PROSPECTS FOR THE DEVELOPMENT OF ACCOUNTING IN THE ECONOMY - Xudayarov , Rashid; Sattarova , Madina (Effective scientific journals, 2025)
This article examines the future prospects of accounting in developing economies, highlighting its indispensable role in ensuring transparency, financial stability, and sustainable growth. Special emphasis is placed on the Central Asian region, which provides a unique example of post-Soviet transition, modernization, and integration into the global economy. Drawing on statistical data from the World Bank, IMF, IFAC, and regional government reports, the study shows that the importance of accounting does not decline in developing economies; instead, it intensifies as markets mature and investment flows increase. The article also emphasizes the critical role of auditing in safeguarding public and private resources, attracting foreign direct investment (FDI), and promoting good governance. Historical lessons, global experience, and digital innovation are analyzed to show that the accounting profession remains one of the most essential pillars of long-term economic development.